ON THE QUESTION OF THE INVESTIGATION OF THE CONTROL OF THE FINANCING OF THE ELECTIONS OF THE NATIONAL DEPUTY OF UKRAINE - Вигівська, А. С. (Київський національний університет імені Тараса Шевченка, 2021)
The article is devoted to the constitutional and legal means of control over the process of financing the preparation and conduct of elections of people's deputies of Ukraine to the Verkhovna Rada of Ukraine and analyzes the combination of current legislation of Ukraine and international acts. Special attention is paid to the Electoral Code of Ukraine, as the main codified normative legal act in the field of electoral law.

Стаття присвячується конституційно-правовим засобам контролю за процесом фінансування підготовкою та проведенням виборів народних депутатів України до Верховної Ради України та проаналізовано поєднання норм чинного законодавства України та міжнародних актів. Окрему увагу приділено Виборчому Кодексу України, як основному кодифікованому нормативно-правовому акту у сфері виборчого права.
ДО ПИТАННЯ ДОСЛІДЖЕННЯ КОНТРОЛЮ ЗА ФІНАНСУВАННЯМ ВИБОРІВ НАРОДНИХ ДЕПУТАТІВ УКРАЇНИ
Keywords: elections; people's deputies of Ukraine; election financing. control over election financing.; вибори; народні депутати України; фінансування виборів. контроль за фінансуванням виборів.